2018
DOI: 10.1186/s12864-018-5037-7
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide identification of tissue-specific long non-coding RNA in three farm animal species

Abstract: BackgroundNumerous long non-coding RNAs (lncRNAs) have been identified and their roles in gene regulation in humans, mice, and other model organisms studied; however, far less research has been focused on lncRNAs in farm animal species. While previous studies in chickens, cattle, and pigs identified lncRNAs in specific developmental stages or differentially expressed under specific conditions in a limited number of tissues, more comprehensive identification of lncRNAs in these species is needed. The goal of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
84
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(98 citation statements)
references
References 79 publications
11
84
3
Order By: Relevance
“…Using the TopHat (http://ccb.jhu.edu/software/tophat/index.shtml) and Cufflinks (http: //cole-trapnell-lab.github.io/cufflinks/releases/v2.1.1) programs, 86.3-89.5% of all the reads were successfully mapped against the current reference horse genome EquCab3.0. After developing the bioinformatics pipeline for processing the large amounts of transcriptome sequences, 1464 multiple-exon lncRNAs were identified in the placentas of YL and NQ breeds, and 361 of them overlapped with a previous study [7], which did not contain the placenta tissue, supporting the tissue-specific expression of lncRNAs [27]. We identified 107 lncRNAs as being differentially expressed between the YL and NQ breeds.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…Using the TopHat (http://ccb.jhu.edu/software/tophat/index.shtml) and Cufflinks (http: //cole-trapnell-lab.github.io/cufflinks/releases/v2.1.1) programs, 86.3-89.5% of all the reads were successfully mapped against the current reference horse genome EquCab3.0. After developing the bioinformatics pipeline for processing the large amounts of transcriptome sequences, 1464 multiple-exon lncRNAs were identified in the placentas of YL and NQ breeds, and 361 of them overlapped with a previous study [7], which did not contain the placenta tissue, supporting the tissue-specific expression of lncRNAs [27]. We identified 107 lncRNAs as being differentially expressed between the YL and NQ breeds.…”
Section: Discussionmentioning
confidence: 51%
“…Other studies showed the strong association of LCORL/NCAPG, HMGA2, PROP1, LASP [39], ZFAT, DIAPH3 [40], ACTN2, ADAMTS17, GH1, ANKRD1 [40], and ACAN [41,42] with miniature size and dwarfism in a variety of pony breeds, including Shetland [41,43], miniature [44], Welsh ponies [45], German warmblood horses [46], American miniature horses, Brazilian ponies [47], and Jeju ponies [48], as well as B4GALT7 [49] and PROP1 [50] in Friesian horses. These genes were not found in this study, which may be due to the expression specificity of lncRNAs in different horse breeds [27] and different omics levels, since TBX3, under strong selection in Chinese ponies, was also identified in this study. This indicated that more breeds and samples are needed to analyze growth regulation during horse development.…”
Section: Discussionmentioning
confidence: 57%
“…Using the RNA-seq technology, previous studies have identified 4404, 2481, 39,907, 8691, 1376, 6543, 2597 and 2056 lncRNAs in breast muscle, spleen, cerebrum, ovarian follicle, trachea, liver, testis and adipose of chickens, respectively [33,[92][93][94][95][96][97][98]. Moreover, Kern et al [99] found 9393 lncRNAs in eight tissue types (adipose, cerebellum, cortex, hypothalamus, liver, lung, skeletal muscle and spleen) of chickens and Hong et al [100] obtained 6900 lncRNAs genes in 20 different tissues (breast, gizzard, liver, pancreas, uterus, heart, bone marrow, kidney, cerebrum, cerebellum, eye, immature egg, mature egg, gall-bladder, comb, shank, skin, lung, spleen and fascia) of an individual Ogye, with c.75% of lncRNAs as tissue-specific. In the present study, 818 candidate lncRNAs were identified in the mid-segments of chicken small intestines.…”
Section: Discussionmentioning
confidence: 99%
“…org) aims to support and coordinate the community in the endeavor of creating reference functional maps of the genomes of domesticated animals across different species, tissues and developmental stages, with an initial focus on farm and companion animals [12][13][14][15]. To achieve high quality functional annotation of these genomes, FAANG carries out activities to standardize core biochemical assay protocols, coordinate and facilitate data sharing.…”
Section: Introductionmentioning
confidence: 99%